How Emotional Intelligence Influences Cognitive Outcomes Among University Students: The Mediating Role of Relational Engagement During the Covid-19 Pandemic - Iqbal, Javed; Ashraf, Muhammad Azeem; Perveen, Shahnaz; Qureshi, Naima; Imran, Zahid; Jin, Ning (Frontiers in Psychology, 2021)
This study investigated the relationships between emotional intelligence, relational engagement, and cognitive outcomes. A survey questionnaire containing 34 statements was completed by 338 undergraduate students from four Chinese universities, with responses recorded on a 7-point Likert-type scale. The relationships were examined using partial least squares structural equation modeling. The findings showed that emotional intelligence influenced cognitive outcomes directly and indirectly during the pandemic. In the forms of self-regulation and social skills, high levels of emotional intelligence improved students’ cognitive outcomes. Further, aspects of emotional intelligence including self-regulation, self-awareness, empathy, motivation, and social skills were found to improve students’ relational engagement. Relational engagement was positively correlated with cognitive outcomes, indicating its potential for improving critical thinking among university students. Finally, relational engagement was found to be a key mediator of the relationship between emotional intelligence and cognitive outcomes. It is concluded that students with higher levels of emotional intelligence and relational engagement may achieve better cognitive outcomes. The implications of the research and suggestions for future studies are also discussed.